The yeasts of the genus Spathaspora: potential candidates for second‐generation biofuel production. Issue 2 (11th October 2017) - Cadete, Raquel M.; Rosa, Carlos A.
Abstract: Yeasts of the Spathaspora clade have the ability to convertd ‐xylose to ethanol and/or xylitol. This is an important trait, as these yeasts may be used to produce bioethanol from lignocellulosic biomass or as a source of newd ‐xylose metabolism genes for recombinant industrial strains of Saccharomyces cerevisiae . The core group of the genus Spathaspora has 22 species, both formally described and not yet described. Other species, such as Sp. allomyrinae, Candida alai, C. insectamans, C. lyxosophila, C. sake, Sp. boniae and C. subhashii are weakly associated with this clade, based on LSU rRNA gene D1/D2 sequence analyses. Spathaspora passalidarum, Sp. arborariae, Sp. gorwiae and Sp. hagerdaliae produce mostly ethanol fromd ‐xylose, whereas the remaining species within the Spathaspora clade already tested for this property may be considered xylitol producers. Among thed ‐xylose‐fermenting Spathaspora species, Sp. passalidarum is the best ethanol producer, displaying high ethanol yields and productivities when cultured in media supplemented with this pentose under oxygen‐limited or anaerobic conditions. The species also exhibits rapidd ‐xylose consumption and the ability to ferment glucose, xylose and cellobiose simultaneously. These characteristics suggest that Sp. passalidarum is a potential candidate for domestication and use in the fermentation of lignocellulosic materials. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Yeasts of the Spathaspora clade have the ability to convert d‐xylose to ethanol and/or xylitol. The core group of the genus Spathaspora has 22 species, both formally described and not yet described. Among the d‐xylose‐fermenting Spathaspora species, Sp. passalidarum is the best ethanol producer, displaying high ethanol yields and productivities, which suggests this species as a potential candidate for domestication and use in the fermentation of lignocellulosic materials.